2016
DOI: 10.1007/jhep07(2016)100
|View full text |Cite
|
Sign up to set email alerts
|

Tensor networks from kinematic space

Abstract: We point out that the MERA network for the ground state of a 1+1-dimensional conformal field theory has the same structural features as kinematic space-the geometry of CFT intervals. In holographic theories kinematic space becomes identified with the space of bulk geodesics studied in integral geometry. We argue that in these settings MERA is best viewed as a discretization of the space of bulk geodesics rather than of the bulk geometry itself. As a test of this kinematic proposal, we compare the MERA represen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
165
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(169 citation statements)
references
References 70 publications
4
165
0
Order By: Relevance
“…In other words, it is rather more natural to think of M as a de Sitter-type space [48][49][50]. Equivalently, one should regard the approach of the previous section as the Wick-rotated Euclidean version of the approach described here.…”
Section: Jhep12(2016)055mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, it is rather more natural to think of M as a de Sitter-type space [48][49][50]. Equivalently, one should regard the approach of the previous section as the Wick-rotated Euclidean version of the approach described here.…”
Section: Jhep12(2016)055mentioning
confidence: 99%
“…. , 99} and t is chosen uniformly in the interval [0,50]. To determine if a pair of such events was causally connected we calculated the commutator quantity…”
Section: Jhep12(2016)055mentioning
confidence: 99%
“…This inspired many subsequent works that attempt to make further concrete connection between the AdS/CFT and the tensor network. It is for example observed that the MERA tensor network, that originally inspired Swingle's observation [3], is connected to the space of geodesics in AdS space, termed the kinematic space [4][5][6][7][8][9][10][11][12]. 1 More recently, [31] proposes a concrete construction of a tensor network such that the entanglement entropy of the physical degrees of freedom is given precisely by the size of a minimal surface that cuts through the bulk of the tensor network.…”
Section: Jhep08(2016)086 1 Introductionmentioning
confidence: 99%
“…space [7,8]. This proposal is inspired by the study of the hole entropy in the bulk from dual CFT data, which suggests a way to define the bulk geometry from differential entropy [11][12][13][14][15][16][17][18].…”
Section: Jhep01(2017)092mentioning
confidence: 99%
“…It has been widely suspected that the holographic entanglement entropy could play a pivotal role in constructing bulk spacetime and even bulk physics. There are several proposals to construct the bulk geometry from boundary CFT, mainly based on the concept of the tensor network [4][5][6][7][8][9][10]. Among them, one promising approach proposed by B. Czech et al is to view the MERA (Multi-scale Entanglement Renormalization Ansantz) tensor network as a discrete version of vacuum kinematic…”
Section: Introductionmentioning
confidence: 99%